Association Between Circulating Regulator of Calcineurin 2 Concentrations With Overweight and Obesity - Wang, Hongya; Fang, Xia; Ren, Qian; Zeng, Yan; Tan, Xiaozhen; Ye, Ting; Fan, Jiahao; Xu, Yong (Frontiers in Endocrinology, 2022)
Abstract Background: Regulator of calcineurin 2 (RCAN2) has been reported to promote food intake and weight gain in animal studies. However, its effect on body weight in humans is unclear. Objective: This study aimed to investigate the relationship between serum RCAN2 concentrations and participants with overweight/obesity. Methods: A cross-sectional study was performed in 872 Chinese adults, including 348 participants with normal weight (NW), 397 participants with overweight (OW), and 127 participants with obesity (OB). All participants were divided into NW, OW and OB groups according to their body mass index (BMI). Serum RCAN2 concentrations were determined by enzyme-linked immunosorbent assay. Results: Serum RCAN2 concentrations gradually increased with the increase of BMI (p < 0.001). The percentages of OW/OB gradually increased in tandem with increasing tertiles of RCAN2 (p < 0.001). Additionally, serum RCAN2 concentrations were significantly correlated with a series of anthropometric and metabolic parameters, predominantly including body weight, BMI, SBP, DBP, total cholesterol, triglycerides, HDL-C, LDL-C (all p < 0.05). Furthermore, logistic regression analysis showed that the risk of OW/OB was significantly increased with the increase of serum RCAN2 concentrations. Receiver operation characteristic (ROC) curve analysis revealed that serum RCAN2, especially serum RCAN2/(AST/ALT) ratio, might serve as a candidate biomarker for obesity. Conclusion: Serum RCAN2 concentrations were increased in subjects with OW/OB. The increased serum RCAN2 concentrations were associated with the increased risks of OW/OB.